Prevalence of workplace violent episodes experienced by nurses in acute psychiatric settings - Niu, Shu-Fen; Kuo, Shu-Fen; Tsai, Hsiu-Ting; Kao, Ching-Chiu; Traynor, Victoria; Chou, Kuei-Ru (PloS one, 2019)
Nurses who experience workplace violence exhibit compromised care quality and decreased work morale, which may increase their turnover rate. This study explored prevalence of workplace violence, the reaction of victims, and workplace strategies adopted to prevent violence among acute psychiatric settings in northern Taiwan. A cross-sectional study was conducted, which consisted of 429 nurses who completed the Chinese version of the Workplace Violence Survey Questionnaire developed by the International Labor Office, International Council of Nurses, World Health Organization, and Public Services International. The rates of physical and psychological violence were 55.7% and 82.1%, respectively. Most perpetrator of the workplace violence were patients. Most victims responded by instructing the perpetrator to stop, followed by narrating the incident to friends, family, and colleagues. Only 4.9%-12% of the victims completed an incident or accident form, and the main reason for not reporting these violent incidents was the belief that reporting such incidents was useless or unimportant. The major strategies adopted by workplaces to prevent violence were security measures, patient protocols, and training. Institutions should train staff to handle violence, provide a therapeutic environment, simplify the reporting process, and encourage reporting of all types of violence.